DFT, FT-IR and FT-Raman investigations of 1-methyl-2-imidazolecarboxaldehyde - Polat, Turgay; Yurdakul, Şenay (Elsevier BV, 2013)
Abstract The FT-IR and FT-Raman spectra of 1-methyl-2-imidazolecarboxaldehyde were recorded in the region 4000–400 cm −1 and 3500–50 cm −1 , respectively. Optimized geometric parameters, conformational equilibria, normal mode frequencies, and corresponding vibrational assignments of title molecule were examined by means of density functional theory (DFT) method with B3LYP/6-311++G(d,p) basis set. All vibrational frequencies were assigned in detail with the help of total energy distribution (TEDs). The results showed that the DFT/B3LYP method predics vibrational frequencies and the structural parameters effectively. Furthermore, solvent effects are investigated in different solvents (chloroform, dimethylsulfoxide and water) using the self-consistent isodensity polarizable continuum model (SCI-PCM). All results indicate that the combination of SCI-PCM model and DFT/B3LYP/6-311++G(d,p) calculation could give excellent explanations of the solvent effects. Intermolecular hydrogen bonding between 1-methyl-2-imidazolecarboxaldehyde and water was investigated using quantum chemical methods. DFT calculations were used to optimize the adducts of heterocycle with the single water molecule.